Revisión de los cricétidos de talla media del Mioceno del área Daroca-Villafeliche en la cuenca de Calatayud-Teruel (Zaragoza,España) - Peláez-campomanes, Pablo; Daams, Remmert; Jan van der Meulen, Albert (Coloquios de Paleontología, 2003)
Revision of Democricetodon (excluding D. sulcatus and D. cf gaillardi), Fahlbuschia, Pseudofahlbuschia and Renzimys from the Aragonian type area (Spain) results in the synonymization of the four genera, Democricetodon prevailing according to the rules of priority. Democricetodon decipiens is synonymized with D. corcolesi, D. darocensis with D. larteti, and Renzimys bilobatus with D. crusafonti. One new species of Democricetodon (D. moralesi n.sp.) is defined.Two partly contemporaneous evolutionary lineages are recognized: the Democricetodon hispanicus - D. lacombai lineage (D. hispanicus-D. moralesi n.sp.-D. jordensi-D. lacombai) and the Democricetodon franconicus - D. crusafonti lineage (D. franconicus-D. koenigswaldi-D. larteti- D. crusafonti).